ASUHAN KEPERAWATAN PADA KLIEN DIABETES MELITUS TIPE 2 DENGAN MASALAH KETIDAKSTABILAN KADAR GLUKOSA DARAH DI WILAYAH CIRACAS, JAKARTA TIMUR - Nur Safitriani (2023)
Background: Diabetes mellitus is a chronic health problem or non-communicable disease caused by damage to the pancreas so that it cannot produce insulin optimally. The prevalence of diabetes estimates an increase of up to 19.9% or 111.2 million people aged around 65-79 years. The high prevalence of diabetes melitus every year for diabetics is caused by several factors, for example gender, marital status, level of education, occupation, physical activity, unhealthy lifestyle, body mass index and age. One suggestion to reduce blood glucose levels in carrying out nursing care for people with diabetes mellitus is through physical exercise, diabetes mellitus foot exercises. Research method: this study uses qualitative methods in the form of interviews, direct observation of clients with a sample of 1 respondent throughout the month of March with an 11-day visit. Results: The results of the study showed that blood glucose level instability was associated with insulin resistance during the 6th visit, resolved impaired skin/tissue integrity associated with peripheral neuropathy during the 4th visit, and impaired physical mobility associated with joint stiffness during the 3rd day. Conclusion: in carrying out this nursing care the researcher does it to the maximum extent possible, it is hoped that the results obtained will be maximum